Impact of prognostic nutritional index on long-term outcomes in patients with breast cancer. Issue 1 (December 2016) - Mohri, Tomomi; Mohri, Yasuhiko; Shigemori, Tsunehiko; Takeuchi, Kenji; Itoh, Yoshiyuki; Kato, Toshio
Abstract Background Prognostic nutritional index has been shown to be a prognostic marker for various solid tumors. However, few studies have investigated the impact of the prognostic nutritional index on survival of patients with breast cancer. The aim of this study was to investigate the impact of the prognostic nutritional index on the long-term outcomes in patients with breast cancer. Methods This study reviewed the medical records of 212 patients with breast cancer who underwent mastectomy. The prognostic nutritional index was calculated as 10 × serum albumin (g/dl) + 0.005 × total lymphocyte count (per mm3 ). Receiver operating characteristic curve analysis was performed to determine the cutoff value of the prognostic nutritional index. The survival curves were calculated by the Kaplan–Meier method. Differences between the curves were analyzed by the log-rank test. Multivariate Cox proportional hazard model was used to evaluate the prognostic significance of prognostic nutritional index in patients with breast cancer. Results The mean prognostic nutritional index just before the operation was 51.9, and the median follow-up after surgery was 47.7 months. The optimal cutoff value of the prognostic nutritional index for predicting the overall survival was 52.8 from the receiver operating characteristic curve analysis. The 5-year overall survival rate was 98.3 % in the prognostic nutritional index >52.8 and 92.0 % in the prognostic nutritional index <52.8 (P = 0.013). In the multivariate analysis, a low prognostic nutritional index was an independent predictor for poor overall survival (HR, 5.88; 95 % CI, 1.13–108.01;P = 0.033). Conclusions The prognostic nutritional index is a simple and useful marker for predicting the long-term outcomes of breast cancer patients, independent of the tumor stage.